Analisis Manajemen Persediaan Dalam Inovasi Pada Kedai Sultan Karawang - Muhammad Arrizky Ilham As’ad; Muhamad Fakhri Abdul Aziz; Darma Karen Yudhsitira; Tantri Tri Astuti; Ujang Suherman (CV. Lenggogeni Data Publishing, 2024)
The aim of this research is to analyze product innovation and business innovation at the Karawang Sultan shop. This research uses a qualitative research design. The qualitative method is a research method that uses data in the form of numbers and the collected data is analyzed using qualitative analysis. The results of this research, the success of Kedai Sultan's business can be seen from its good and very friendly service, its prices which are quite affordable, and most importantly, the innovation of this shop which can create dishes with large portions and delicious taste quality is the most important factor for This shop is always busy with customers. Keywords: inventory, innovation